The molecular characterization of a depurinated trial DNA sample can be a model to understand the reliability of the results in forensic genetics. Issue 21 (31st October 2014) - Fattorini, Paolo; Previderè, Carlo; Sorçaburu‐Cigliero, Solange; Marrubini, Giorgio; Alù, Milena; Barbaro, Anna M.; Carnevali, Eugenia; Carracedo, Angel; Casarino, Lucia; Consoloni, Lara; Corato, Silvia; Domenici, Ranieri; et al.
<x xml:space="preserve">Abstract</x> The role of DNA damage in PCR processivity/fidelity is a relevant topic in molecular investigation of aged/forensic samples. In order to reproduce one of the most common lesions occurring in postmortem tissues, a new protocol based on aqueous hydrolysis of the DNA was developed in vitro. Twenty‐five forensic laboratories were then provided with 3.0 μg of a trial sample (TS) exhibiting, in mean, the loss of 1 base of 20, and a molecular weight below 300 bp. Each participating laboratory could freely choose any combination of methods, leading to the quantification and to the definition of the STR profile of the TS, through the documentation of each step of the analytical approaches selected. The results of the TS quantification by qPCR showed significant differences in the amount of DNA recorded by the participating laboratories using different commercial kits. These data show that only DNA quantification "relative" to the used kit (probe) is possible, being the "absolute" amount of DNA inversely related to the length of the target region (r2 = 0.891). In addition, our results indicate that the absence of a shared stable and certified reference quantitative standard is also likely involved. STR profiling was carried out selecting five different commercial kits and amplifying the TS for a total number of 212 multiplex PCRs, thus representing an interesting overview of the different analytical protocols used by the participating laboratories. Nine laboratories decided to characterize the TS using a single kit, with a number of amplifications varying from 2 to 12, obtaining only partial STR profiles. Most of the participants determined partial or full profiles using a combination of two or more kits, and a number of amplifications varying from 2 to 27. The performance of each laboratory was described in terms of number of correctly characterized loci, dropped‐out markers, unreliable genotypes, and incorrect results. The incidence of unreliable and incorrect genotypes was found to be higher for participants carrying out a limited number of amplifications, insufficient to define the correct genotypes from damaged DNA samples such as the TS. Finally, from a dataset containing about 4500 amplicons, the frequency of PCR artifacts (allele dropout, allele drop‐in, and allelic imbalance) was calculated for each kit showing that the new chemistry of the kits is not able to overcome the concern of template‐related factors. The results of this collaborative exercise emphasize the advantages of using a standardized degraded DNA sample in the definition of which analytical parameters are critical for the outcome of the STR profiles.